Problems Of Mathematics Learning On The Alef Platform In Class VII MTs Negeri 4 Kutai Kartanegara - Devi Fitriyati; Asyril Asyril; Nanda Arista Rizki (Faculty of Teacher Training and Education, Mulawarman University, 2022)
This study aims to find out the problems of teachers, students, and teacher efforts in facing problems in the implementation of mathematics learning on the Alef Platform in class VII MTs Negeri 4 Kutai Kartanegara. This is based on problems in learning mathematics with the use of the Alef Platform. Alef Platform is a learning medium specifically designed to engage students by providing a learning experience by watching videos, playing, and practicing questions. This research is qualitative study with Miles and Huberman model. Data were collected uses observation, interviews, and documentation and data validated by uses triangulation techniques. Based on the results obtained, (1)Problems experienced by teachers were the implementation of the learning process in the preliminary activities were still not smooth, lack of creativity of teachers when using the media, teachers cannot reduce the learning features, lack of objective learning outcomes, and the lack of an objective assessment on the Alef Platform. (2)The Problems experienced by students were the number of students who forgot the password, the learning video looked very monotonous, the game features were not in accordance with the ability of students, the questions presented on the Alef Platform were so difficult to lead students to a lazy condition of doing the questions so that student’s learning motivation decreased, the student did not see the existing explanations if the student answered the wrong practical feature, and students cannot ask if having difficulty to the Alef Platform. (3)Efforts made by teachers to overcome the problem that the teacher always gave directions to the writing forgot password, how to download documents, and the teacher re-explained the material that had not been understood by the students.